2017
DOI: 10.1136/sextrans-2017-053434
|View full text |Cite
|
Sign up to set email alerts
|

Sexual relationships, intimate partner violence and STI partner notification in Cape Town, South Africa: an observational study

Abstract: ObjectivesWe aimed to identify individual and sexual partnership characteristics associated with partner notification (PN) among people with STI. We hypothesised that PN would be less likely in more casual sexual partnerships and in partnerships with intimate partner violence (IPV).MethodsWe conducted an observational study among the first 330 patients with STI enrolled in a trial of a behavioural intervention to reduce STI incidence, at a clinic in a poor, Cape Town community. We included 195 index patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…9 In another study at a community-based clinic in South Africa, participants reported notifying only 64% of partners of their STI diagnosis. 10 Among South Africans, fears of intimate partner violence and relationship dissolution have been identified as barriers to partner notification following diagnosis with a STI. 11,12 Others have been conducting research on how best to optimize STI management, including partner notification, in South Africa since the late 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…9 In another study at a community-based clinic in South Africa, participants reported notifying only 64% of partners of their STI diagnosis. 10 Among South Africans, fears of intimate partner violence and relationship dissolution have been identified as barriers to partner notification following diagnosis with a STI. 11,12 Others have been conducting research on how best to optimize STI management, including partner notification, in South Africa since the late 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…21 While the optimal method for partner notification is unknown in South Africa and similar settings, the latest South Africa National Strategic Plan for HIV, TB, and STIs outlines the need to assess ideal partner notification methods and focus on key populations, including adolescent girls and young women. 22 This issue is of great importance for young people, who are less likely to notify their partners of STIs compared with older adults, [23][24][25][26] likely contributing to STI recurrence rates of up to 60% among South African youth. 27 The limits of syndromic STI management among youth, 11,[27][28][29][30][31] alongside the current lack but ongoing development of cost-effective, point-of-care diagnostics, 32 support the argument for lower-resourced settings to consider laboratory-based STI screening, and thus appropriate medications for individuals and their sexual partners for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…GBV-associated HIV transmission may be compounded over the sexual life course of AGYW [45] as repeated acts of violence perpetrated by more than one partner are commonly reported [46,47]. While cases of IPV linked directly to HIV PN have not been reported following HIV PN among adult women in the literature [48][49][50][51], the risk of IPV following HIV PN may be greater for AGYW and must be monitored.…”
Section: Risk Of Intimate Partner Violencementioning
confidence: 99%